With apology, not with glee : caning as judicial corporal punishment in post-independence Singapore - Lim, Rebekah Jia Yi (2018)
This research explores the history of judicial corporal punishment in Singapore from its colonial institution to the end of the millennium. It examines the caning of Michael Fay in 1994 within the context of Singapore’s post-independence trajectory. While describing chronologically the development of caning as a Singaporean institution in the 1990s, this paper articulates the fluid and changing nature of identity and society in Singapore. Throughout, it asks: what are the motivations for judicial corporal punishment, how has it been understood, and how have the answers to these questions been found, negotiated and contested? It finds that tensions apparent in the 1990s are entwined with and shaped by the context of the colonial and post-independence years. Within, the role of the government and of society in moderating each other informed how society came conceptualise and express its understanding of caning. Over the decades, judicial caning in Singapore has expanded and multiplied in meaning. In identifying and questioning those meanings, this paper articulates also a parallel narrative of socio-political change in Singapore.